The Euromediterranean industrial cooperation process: recent developments a parallel example - Picchioni S. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The Euromediterranean partnership on industry was launched in 1996 through the 1st Euromediterranean Conference of Industry Ministers. The objective of the Conference was to define an industrial cooperation policy at bilateral and regional level aimed at fostering the economic and industrial development of the Mediterranean partner countries, at promoting foreign direct investments in the Region and the North-South and South-South exchange. In order to make regional cooperation more effective and incisive last October the Italian government organised the 5th Euromediterranean Conference of Industry Ministers that was held in Caserta. The Conference marked an important moment to revitalise the political dialogue on Euromediterranean cooperation, stressing the importance of a common engagement of public authorities and the private sector.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)